PENGEMBANGAN E-LKPD BERBASIS TPACK PADA PEMBELAJARAN IPAS MATERI BAGIAN TUMBUH – TUMBUHAN KELAS IV SD - Aida Afriany; Tiflatul Husna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to produce media, analyze the feasibility of using E-LKPD and analyze student responses to TPACK-based E-LKPD on plant parts material. The researcher used the R&D (research and development) research method. This type of research refers to development research. This research will later produce a certain type of product which will then be tested for the effectiveness of the media that has been made (Bulu & Muhsam, n.d.). The feasibility of the TPACK-based chemistry E-LKPD development product on plant material can be seen based on the validation results by media experts and material experts. The results obtained showed scores of 60 and 75 which were in the very valid category and were feasible to be tested. The results of student responses to the TPACK-based science E-LKPD development product using plant parts material which was tested in small groups with 10 students obtained a percentage of 95% with a very feasible category. So it can be stated that the product developed is feasible to be used as a teaching material. The E-LKPD IPAS product based on TPACK plant material produced is declared feasible,